2000
DOI: 10.1002/1098-2361(2000)19:5<347::aid-zoo6>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive endocrine monitoring of elephants: An essential tool for assisting captive management

Abstract: Considerable information now is available about the basic reproductive biology of elephants, especially females. However, as important as this knowledge is, it no longer is enough to simply compile it into a database. The potential exists for using endocrine monitoring techniques to solve real problems. This review summarizes our current knowledge of elephant endocrinology and offers suggestions on how to use the technology to maximize reproductive potential. The estrous cycle can be monitored through the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
123
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 53 publications
8
123
1
2
Order By: Relevance
“…Phase length estimates as well as ovarian cycle length estimates are given as mean ± SD. Females were categorized as having an irregular cycle when overall cycle length exceeded or fell short of the reported norm of 13 to 17 weeks [10,[17][18][19][20][21][22][23][24][25]. The non-cycling category was reserved for females who had no identifiable pattern in 5-pregnan-3-ol-20-on concentrations throughout the study period [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase length estimates as well as ovarian cycle length estimates are given as mean ± SD. Females were categorized as having an irregular cycle when overall cycle length exceeded or fell short of the reported norm of 13 to 17 weeks [10,[17][18][19][20][21][22][23][24][25]. The non-cycling category was reserved for females who had no identifiable pattern in 5-pregnan-3-ol-20-on concentrations throughout the study period [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the female African elephant (Loxodonta africana), estrous cycle length is reported to range between 13 to 17 weeks [17][18][19][20][21][22][23][24][25]. The cycle is divided into a 4 to 6 week follicular phase after 4 which an increase in progesterone levels, believed to trigger ovulation, marks the onset of an 8 to 11 week luteal phase [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Much has been learned about the reproductive endocrinology of elephants in the past decade, and this has contributed significantly to improved breeding management (see reviews, Hodges, 1998;Brown, 2000Brown, , 2006. While most of the initial work was based on analyses of circulating hormones, more recent studies have shown the utility of urine and faecal steroid metabolite assessments for noninvasive monitoring of gonadal function in the elephant (Heistermann et al, 1997;Fiess et al, 1999;Czekala et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another hormonal indicator is a marked increase in prolactin immunoactivity after 5 months of gestation (Brown, 2000(Brown, , 2006. The diagnostic advantage of prolactin is that only a single sample is needed after 5 months, compared to the longitudinal sampling that is necessary for pregnancy diagnosis with progestagens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation